2013
DOI: 10.1111/ajt.12131
|View full text |Cite
|
Sign up to set email alerts
|

Colonization With Small Conidia Aspergillus Species Is Associated With Bronchiolitis Obliterans Syndrome: A Two-Center Validation Study

Abstract: Aspergillus colonization after lung transplantation may increase the risk for bronchiolitis obliterans syndrome (BOS), a disease of small airways. We hypothesized that colonization with small conidia Aspergillus species would be associated with a greater risk of BOS, based upon an increased likelihood of deposition in small airways. We studied adult primary lung recipients from two large centers; 298 recipients at University of California, Los Angeles and 482 recipients at Duke University Medical Center. We gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 24 publications
2
99
1
3
Order By: Relevance
“…This is important because we have previously reported that Aspergillus colonization is a risk factor for CLAD. 18,19 Without direct evidence until now, we have surmised that Aspergillus colonization causes subclinical injury and inflammation, which can initiate and propagate dysregulated repair mechanisms leading to CLAD. In this study, we confirm that Aspergillus colonization is dominated by differential expression of genes pertaining to defense response, response to wounding, and inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is important because we have previously reported that Aspergillus colonization is a risk factor for CLAD. 18,19 Without direct evidence until now, we have surmised that Aspergillus colonization causes subclinical injury and inflammation, which can initiate and propagate dysregulated repair mechanisms leading to CLAD. In this study, we confirm that Aspergillus colonization is dominated by differential expression of genes pertaining to defense response, response to wounding, and inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Given our prior work showing that Aspergillus colonization is a risk factor for CLAD, 18,19 it is interesting that BAL neutrophilia is also described as a precursor to CLAD. 36,37 However, in this study, Aspergillus colonized cases who developed CLAD did not have a greater proportion of BAL neutrophils than those who remained CLAD free.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Potential mechanisms of allograft injury by CARVs in lung transplant recipients include upregulation of inflammatory cytokine production initiated by viral replication or a direct cytopathic effect on the respiratory epithelium (134). Although some authors described a trigger for acute rejection after CARV infections and a higher risk of subsequently developing BOS (133,135), data in the literature are conflicting (136)(137)(138)(139). Based on a pooled analysis including all clinical studies evaluating the role of CARVs on lung allograft outcomes, the main conclusions were that infection with CARVs was not associated with significantly higher incidence of subsequent acute rejection (odds ratio [OR] 1.35; 95% confidence interval [CI] 0.41-4.43) and that a nonsignificant higher incidence of BOS in patients with viral infection was observed (18% vs. 11.6%) (136) (Figure 2).…”
Section: Infection By Community-acquired Respiratory Virusesmentioning
confidence: 99%